The Influence Of Product Quality And Service Quality On The Decision To Purchase Honda Beat Motorcycles In Palembang City - Ramadhani, Karmelia Putri; Naruliza, Esty; Effendi, RY. (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study aims to determine the influence of product quality and service quality on the purchase decision of Honda Beat Motorcycle in Palembang City. The background of this research is that the Honda Beat is in the spotlight after netizens somplained that the motorcycle frame was rusty and broken. This type of research uses a quantitative descriptive approach. The data used in this study is primary data by distributing a questionnaire through google form. The sampling technique uses accidental sampling. The sample in this study amounted to 272 respondents “with an error level of 10% or 0.1. The test was carried out in three stages, namely the validity and reliability test, the classical assumption test and the hypothesis test using the 2025 version of SPSS. The results of the study show that the value of the determination coefficient (R²) of 0.570 means that the dependent variable of the purchase decision can be explained by the independent variable, namely Quality and Quality of Service. So the contribution of independent variables is 57.0%. While the remaining 43% were influenced by other factors that were not analyzed in this study, wich included cultural factors, social factors, personal factors, and psychological factors, as well as advertising and promotional factors.